TINJAUAN REALISASI ANGGARAN DAN CAPAIAN KINERJA PADA BIDANG PERENCANAAN DAN PEMANFAATAN HUTAN DINAS KEHUTANAN PROVINSI KALIMANTAN TENGAH TAHUN 2025 - Rahayu Dwi Lestari; Hadriani; Muhammad Ichsan Diarsyad; Synthia Ferisca; Sifera Patricia Maithy (LPPM STAI Muhammadiyah Probolinggo, 2026)
Accountability reports in government agencies are highly important to evaluate whether work plans have been implemented successfully. This study aims to evaluate the consistency between budget utilization and physical target achievements within the Planning and Forest Utilization Division of the Central Kalimantan Provincial Forestry Department in 2025. The method used is descriptive quantitative by calculating the achievement percentage between realization and the allocated budget. Data were collected directly from the 2025 Budget Realization Report (LRA) and the Government Agency Performance Report (LKIP). The results indicate that budget utilization and work achievements in the Planning Division are not yet optimal. Out of 14 sub-activities analyzed, 4 activities (28.6%) recorded 0% utilization, 5 activities performed below 50%, and only 2 activities managed to achieve targets above 70%. The main problems found in the field include failed tender processes, delays in central government regulations, shifts in regional planning, spatial map data issues, and weather constraints. This study suggests accelerating the preparation of tender documents, strengthening cooperation between agencies, and providing contingency funds to overcome unexpected obstacles in the field.